2019
DOI: 10.1017/s1049023x19004904
|View full text |Cite
|
Sign up to set email alerts
|

Are there Field Triage Criteria that Can Predict Low-Yield Air Medical Transports?

Abstract: Introduction:Air medical transport of trauma patients from the scene of injury plays a critical role in the delivery of severely injured patients to trauma centers. Over-triage of patients to trauma centers reduces the system efficiency and jeopardizes safety of air medical crews.Hypothesis:The objective of this study was to determine which triage factors utilized by Emergency Medical Services (EMS) providers are strong predictors of early discharge for trauma patients transported by helicopter to a trauma cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…One additional study found associations with higher overtriage and lower undertriage when an advanced life support EMS crew was used to transport rather than a basic life support crew 54 . One additional study found that EMS judgment had an inverse association with resource need and may result in overtriage 55 …”
Section: Resultsmentioning
confidence: 99%
“…One additional study found associations with higher overtriage and lower undertriage when an advanced life support EMS crew was used to transport rather than a basic life support crew 54 . One additional study found that EMS judgment had an inverse association with resource need and may result in overtriage 55 …”
Section: Resultsmentioning
confidence: 99%